Fearful futures and haunting histories in women's desistance from crime: a longitudinal study of desistance as an uncanny process - Fredriksson, Tea (Criminology, 2020)
Although desistance is increasingly recognized as a series of complex processes by which individuals transform from offenders into nonoffenders, few desistance scholars have studied this process in depth. In recent years, however, some have begun to explore how desistance is a process rife with setbacks and struggles. Through an analysis of repeated in-depth interviews with ten desisting women, in this study, we have found such struggles to be unsettling and outright frightening. Examples of this were prevalent throughout the women's narratives. The results of our analysis show how frightening aspects of desistance processes stem from making an unfamiliar, normative lifestyle familiar, while unfamiliarizing oneself with a familiar, deviant lifestyle. As such, desistance processes can be conceptualized as uncanny, that is, as pertaining to the frightening and uncertain. Although uncanniness is not a theoretical framework one tends to find in desistance research, it has the potential to develop the understanding of the struggles, fears, and anxieties of desistance processes. Through our analysis, we engage with how uncanniness can nuance established concepts in desistance research. Implications for theory as well as for criminal justice practice are discussed.